2020
DOI: 10.1136/bmjopen-2019-035933
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent corneal erosion in patients with diabetes mellitus in Taiwan: a population-based cohort study

Abstract: ObjectiveTo investigate the risk of recurrent corneal erosion (RCE) in patients with diabetes mellitus (DM).Design, setting and participantsThis retrospective, nationwide, matched cohort study included 239 854 patients with DM recruited between 2003 and 2005 from the Longitudinal Cohort of Diabetes Patients database. The control group included the same number of age-matched and sex-matched patients without DM selected from the Taiwan Longitudinal Health Insurance Database, 2000. Data for each patient were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
(24 reference statements)
3
8
0
2
Order By: Relevance
“…In this cohort study, we evaluated these comorbidities in AKC patients and discovered that AKC patients with diabetes mellitus had a significantly higher IRR for RCE than the controls ( Table 2 ), and diabetes mellitus was a significant risk factor for the development of RCE in the whole cohort ( Table 3 ). This finding is consistent with several previous studies ( 6 , 7 , 31 ). Nanba et al ( 7 ) conducted a retrospective study including 21 eyes of 21 patients with RCE and found that diabetes mellitus is an important risk factor for RCE.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In this cohort study, we evaluated these comorbidities in AKC patients and discovered that AKC patients with diabetes mellitus had a significantly higher IRR for RCE than the controls ( Table 2 ), and diabetes mellitus was a significant risk factor for the development of RCE in the whole cohort ( Table 3 ). This finding is consistent with several previous studies ( 6 , 7 , 31 ). Nanba et al ( 7 ) conducted a retrospective study including 21 eyes of 21 patients with RCE and found that diabetes mellitus is an important risk factor for RCE.…”
Section: Discussionsupporting
confidence: 94%
“…Further, we found that keratoconjunctivitis sicca is an independent risk factor for the development of RCE in the total cohort ( Table 3 ), although keratoconjunctivitis sicca did not lead to a significantly higher RCE incidence in the AKC patients and controls ( Table 2 ). The association between keratoconjunctivitis sicca and RCE has been reported in several papers ( 31 , 32 ). Our previous study showed the relationship between keratoconjunctivitis sicca and RCE in the total cohort of 239,854 patients with diabetes mellitus and 239,854 matched control ( 31 ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations